Effect of Process Parameters on Material Removal Rate in PMEDM - Nguyen Thai Ha, (International Journal of Scientific Research in Science and Technology, 2025)
The use of powder mixed electrical discharge machining helps overcome this drawback and increases the efficiency of the machining process. This study focused on the machining of SKD61, SKD11, and SKT4 die steels using titanium powder. Taguchi methods and analysis of variance were employed to identify the main parameters that affect the material removal rate (MRR). The other process parameters considered were the electrode material, workpiece material, electrode polarity, pulse-on time, pulse-off time, electric current, and titanium powder concentration. The results indicated that electric current, electrode material, and powder concentration were the most significant parameters that influenced the MRR. A powder concentration of 20 g/l increased the MRR by 42.1%, as compared with no-powder machining.
Keywords: Process Parameters; Material Removal Rate